The Spread Fashion: an Explorative Research of Italian Fashion Blog - Mortara, Ariela; Roberti, Geraldina (Italian Sociological Review, 2017)
In the collaborative context of the web 2.0 the blogging phenomenon has become one of the most common ways to communicate and share information through its user-generated content. In the blogosphere fashion blogs represent probably one of the liveliest segments. Focusing on fashion brands, fashion products, street style, and personal style, fashion blogs can be written by both fashion professionals and normal people with an interest in the fashion system. This phenomenon has become even more relevant since the fashion brands have recognized the role of fashion bloggers in influencing the final consumers as well as the role of peer – to – peer recommendations in shaping desires and attires of fashion blog users. The paper presents the preliminary results of a netnographic analysis conducted on some of the most popular Italian ‘non-professional’ fashion blogs in order to map the different approach to this grassrooted blog phenomenon, and to categorize and interpret the blog postings and the audience comments concerning fashion product-related information.